LANGUAGE TRANSFORMATION ON SOCIAL MEDIA: LINGUISTIC FEATURES OF MODERN ENGLISH - Qodirova , Dilnura; Saitov , Sirojiddin (Scientific practical conference, 2026)
This thesis explores the phenomenon of language transformation in social media, focusing on the linguistic features of modern English. In the digital era, social media platforms have become powerful tools of communication, significantly influencing language use and development. The study examines key aspects such as abbreviations, neologisms, grammatical simplification, and stylistic changes that characterize online communication. It also highlights both the positive and negative impacts of these transformations on language norms and communication effectiveness. Furthermore, the paper discusses how digital communication contributes to the evolution of English as a global language and reflects broader socio-cultural changes.